Composite materials and manufacturing - Cook, Jerome T.; Vaccari, John A. (Fundamental manufacturing processes)
Composites are made up of at least two distinct intended materials - a matrix material, and a reinforcement material. This program explains the relationship between these materials in the production of composite parts, and examines the various composite manufacturing processes, including : manual lay-up, automated lay-up, spray-up, filament winding, pultrusion, and resin transfer molding.